THE ACCOUNTANT AND THE SECURITIES ACT. - Weidenhammer, Robert (The Accounting Review, 1933)
Abstract The article focuses on accountants and the securities act. The significance of the Securities Act of 1933 to the accounting profession can hardly be underestimated. The accounting officer as well as the independent certified public accountant see their public recognition greatly enhanced, but along with this welcome enhancement of standing comes a burden of responsibility that is truly appalling. The risk assumed by an accountant-officer or by a professional accountant, who signs the registration statement submitted to the Securities Commission of the Federal Trade Commission is quite out of proportion to the possible material benefits that may be derived from the service rendered. The Federal Securities Act is the response to demands of a wide majority of the nation. More effective protection of the investor was promised in the platform of the Democratic party as adopted in Chicago in 1932. A general criticism of the act would urge certain restrictions on the civil liabilities and on the other hand certain extensions to make the act a better instrument for the social control of new investments.